Doing implementation research on health governance: a frontline researcher's reflexive account of field-level challenges and their management - Gupteswar Patel; Surekha Garimella; Kerry Scott; Shinjini Mondal; Asha George; Kabir Sheikh (BMC, 2017)
Abstract Background Implementation Research (IR) in and around health systems comes with unique challenges for researchers including implementation, multi-layer governance, and ethical issues. Partnerships between researchers, implementers, policy makers and community members are central to IR and come with additional challenges. In this paper, we elaborate on the challenges faced by frontline field researchers, drawing from experience with an IR study on Village Health Sanitation and Nutrition Committees (VHSNCs). Methods The IR on VHSNC took place in one state/province in India over an 18-month research period. The IR study had twin components; intervention and in-depth research. The intervention sought to strengthen the VHSNC functioning, and concurrently the research arm sought to understand the contextual factors, pathways and mechanism affecting VHSNC functions. Frontline researchers were employed for data collection and a research assistant was living in the study sites. The frontline research assistant experienced a range of challenges, while collecting data from the study sites, which were documented as field memos and analysed using inductive content analysis approach. Results Due to the relational nature of IR, the challenges coalesced around two sets of relationships (a) between the community and frontline researchers and (b) between implementers and frontline researchers. In the community, the frontline researcher was viewed as the supervisor of the intervention and was perceived by the community to have power to bring about beneficial changes with public services and facilities. Implementers expected help from the frontline researcher in problem-solving in VHSNCs, and feedback on community mobilization to improve their approaches. A concerted effort was undertaken by the whole research team to clarify and dispel concerns among the community and implementers through careful and constant communication. The strategies employed were both managerial, relational and reflexive in nature. Conclusion Frontline researchers through their experiences shape the research process and its outcome and they play a central role in the research. It demonstrates that frontline researcher resilience is very crucial when conducting health policy and systems research.